Development of science flipbook to increase student learning activities - Damayanti, Ana Muliana Sri; Nurmayanti, Nurmayanti; Syamsunir, Syamsunir (Journal of Research in Instructional, 2024)
This research aims to find out whether learning resources in the form of science flipbooks can be valid, practical and effective in increasing student activity. With the help of this media, students are encouraged to actively participate in their own learning and gain a deeper understanding of the subject matter. Analysis, planning, development, implementation and evaluation of data collected through observation and questionnaire methods is part of the ADDIE model research development (RnD) approach. This media is "very valid" based on research results which show a media validation level of 96% and a material validation level of 82%. Both teachers and students give high marks to the media because of its usefulness; the teacher gave it 85% and the students 89%, so the combined total was 87.5%. If we look at the use of science flipbook learning media, it can be seen that the level of student activity increased from 59.18% (the "fair" level) at the beginning of class and increased to 77.56% (the "high" level) after using the flipbook. The research conclusion is that the science flipbook learning media has succeeded in making students more involved in learning.